IMAGING–HISTOPATHOLOGICAL CORRELATION OFENDOMETRIAL HYPERPLASIA AND ENDOMETRIAL CARCINOMA - Dr. Ashirwad Pasumarthy; Dr. Tinaimeiru Golmei; Dr. K Raghavendar Babu (Journal of Population Therapeutics and Clinical Pharmacology, 2026)
Background: Endometrial hyperplasia and endometrial carcinoma are important causes of abnormal uterine bleeding. Transvaginal ultrasound (TVUS) provides initial assessment of endometrial thickness and morphology, while MRI can characterize local extent and myometrial invasion in suspected carcinoma. Aim: To evaluate the correlation between endometrial imaging findings and histopathological diagnosis in women undergoing endometrial sampling or hysterectomy. Methods: One hundred women with abnormal uterine bleeding or imaging suspicion of endometrial pathology were evaluated using TVUS; MRI was performed in selected women with suspected or confirmed carcinoma. Endometrial thickness, morphology, focal lesions, vascularity, myometrial interface and cervical extension were recorded. Results: Mean age was 55.2 ± 10.7 years. Postmenopausal bleeding was present in 48%, heavy/prolonged menstrual bleeding in 39% and intermenstrual bleeding in 13%. Histopathology showed benign/atrophic endometrium in 23%, hyperplasia without atypia in 25%, atypical hyperplasia/EIN in 17% and endometrial carcinoma in 35%. Mean endometrial thickness increased from 6.2 mm in benign/atrophic endometrium to 19.6 mm in carcinoma. Among 24 carcinoma patients undergoing MRI, concordance for superficial versus deep myometrial invasion was 87.5%. Conclusion: TVUS is useful for initial detection and risk stratification of endometrial pathology, while MRI provides complementary local staging information in suspected carcinoma. Histopathology remains essential for definitive diagnosis and grading.